Microplastics Generation: Onset of Fragmentation of Polyethylene Films in Marine Environment Mesocosms - Kalogerakis, Nicolas; Karkanorachaki, Katerina; Kalogerakis, G. Calypso; Triantafyllidi, Elisavet I.; Gotsis, Alexandros D.; Partsinevelos, Panagiotis; Fava, Fabio (Frontiers in Marine Science, 2017)
The fragmentation of high-density polyethylene (HDPE) films from single-use supermarket plastic bags to microplastics under laboratory-simulated onshore and nearshore conditions was investigated for a period of 6 months. The weathering process of the plastic strips either on beach sand or in seawater under direct natural sunlight was monitored by tensile strength, molecular weight measurements, FTIR, weight loss and image processing of photographs of the plastic strips before and after mild mechanical stress was applied. The latter represents a novel method proposed for determining the onset of fragmentation through the application of mild mechanical stress on the weathered plastic samples emulating the action of sand and wind on a beach. It was found that 12 h of application of mild mechanical stress in rotating glass bottles filled partially with sand was sufficient time to reach the maximum degree of fragmentation that could occur for the weathered plastics samples being tested. For example, applied mechanical stress yielded an area loss of almost 14% for samples weathered for a period of 5 months and about 16.7% after 5.5 months. While tensile strength tests and molecular weight measurements were rather inconclusive till the very last month when the onset of fragmentation was identified; FTIR measurements revealed that samples under ultraviolet irradiation were gradually modified chemically until fragmentation commenced. After 6 months of weathering, molecular weight measurements showed a 60% reduction for sample SMB-1 whereas for sample SMB-2 the measurement was not possible due to extensive fragmentation. The onset of fragmentation for SMB-1 and SMB-2 samples occurred at a cumulative luminance of 5.3x106 lux•d and in the presence of atmospheric oxygen whereby the polymer films broke down partially to microplastics. When the UV exposure reached 7.2x106 lux•d the weathered plastic strips broke down fully to microplastics with the application of a mild mechanical stress. Samples placed in seawater proved to be resistant to fragmentation compared to those on sand over the six-month period of the weathering experiment. The direct implication of this work is that beached macroplastic debris should be regularly collected from the seashore before they are weathered by sunlight and returned to the